Root Coverage with Coronally Advanced Flap with Connective Tissue Graft: Literature Review and Case Report - Jiménez Bolaños DDS, Francisco J.; Fernández Murillo, Marcelino (Odovtos - International Journal of Dental Sciences, 2017)
The root coverage procedure to treat gingival recessions is the best line of treatment, being the most used the coronal advanced flap. There have been multiple clinical and aesthetic results that cast doubt on whether this procedure by adding a connective tissue graft will be a more predictable and more aesthetic regarding defect removal. In this case report a patient 24-year-old male refers hypersensitivity and aesthetic discomfort in the area of gingival recession. An autologous graft with a coronal flap advancement of connective tissue will be used. After six months of healing the patient reports improvements in: sensitivity, plaque control and aesthetics.